2011
DOI: 10.1111/j.1464-410x.2011.10677.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer active surveillance and health‐related quality of life: results of the Finnish arm of the prospective trial

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Active surveillance is a management option in patients with localized prostate cancer. One concern is the possible psychological burden and quality‐of‐life effects caused by consciousness of living with untreated cancer. Previous studies have reported controversial results about the impact of active surveillance on patient's health‐related quality of life. The data of the present study support the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 33 publications
1
37
1
Order By: Relevance
“…In the same study, it was highlighted that 17 AS patients with subjective perception of disease progression showed worse mental health scores than AS patients without such a perception of disease progression. In the Dutch PRIAS cohort, the baseline mental health score was associated with 9-mo follow-up scores [24] and there were no changes over 9-or 12-mo follow-up in either of the two PRIAS cohorts [24,26]. In summary, these findings do not seem to justify the concern that living with untreated cancer negatively affects the mental health of patients on AS.…”
Section: Mental Healthmentioning
confidence: 80%
See 2 more Smart Citations
“…In the same study, it was highlighted that 17 AS patients with subjective perception of disease progression showed worse mental health scores than AS patients without such a perception of disease progression. In the Dutch PRIAS cohort, the baseline mental health score was associated with 9-mo follow-up scores [24] and there were no changes over 9-or 12-mo follow-up in either of the two PRIAS cohorts [24,26]. In summary, these findings do not seem to justify the concern that living with untreated cancer negatively affects the mental health of patients on AS.…”
Section: Mental Healthmentioning
confidence: 80%
“…No major differences were observed between the HRQoL scores of AS patients and their comparison groups [19,21,23,25,26]. There were also no major changes in HRQoL after 9 or 12 mo on AS in two PRIAS cohorts [24,26].…”
Section: Overall Health-related Quality Of Lifementioning
confidence: 82%
See 1 more Smart Citation
“…One-year analyses of the Finnish arm of the prospective, observational, longitudinal Prostate Cancer Research International: Active Surveillance (PRIAS) study compared general HRQOL, erectile function, urinary function, and mental health before and one year after pursuing active surveillance for low-risk prostate cancer (65). No significant changes were seen in urinary or erectile function, and neither mental nor physical HRQOL declined over time.…”
Section: Qol In Men Choosing Watchful Waiting or Active Surveillancementioning
confidence: 99%
“…This showed no difference in any psychological domain between the surgery and watchful waiting group, but distress was more common in the former. A recent Finnish quality of life study in 126 men on surveillance found that this approach did not provoke short-term quality-of-life disturbances, as assessed by standardized RAND-36, IIEF-5 and IPSS questionnaires [34]. None of the patients changed treatment due to anxiety.…”
Section: Quality Of Lifementioning
confidence: 96%